Moral Hazard Versus Moral Imperative - WU, Chunchi (Institutional Knowledge at Singapore Management University, 1988)
Moral imperative is the opposite of moral hazard. Thus, moral imperative is the drive for an individual to produce more safety when insured than when uninsured. The possibility of moral hazard and moral imperative always exists for any risk averse individual. The cost of safety production plays a critical role in determining the likelihood of moral imperative. The optimal coverage of insurance is shown to depend on the probability of hazards, the insurance premium, and the utility function. The incentives for safety production are shown to depend on the loss, the effectiveness of safety production, and premium loading.